Modeling of Life Expectancy Index in West Nusa Tenggara Province Using Spatial Panel Regression - Baiq Nurul Apriana; Alfira Mulya Astuti; Fadrik Adi Fahrudin (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
One important indicator for evaluating the well-being and standard of living of people in a certain area is the life expectancy index. The goal of this study is to model the life expectancy in the Province of West Nusa Tenggara (NTB). The number of impoverished individuals, adjusted per capita spending, and the average number of years of education are the independent variables used. The data comprised a panel from 10 districts/cities in NTB for the year 2019–2023, obtained from BPS-Statistics NTB Province. The applied analytical method was spatial panel regression, utilizing queen contiguity and a customized weighted matrix based on transportation routes. According to the analysis, a) the spatial autoregressive panel model (SARFEM) was chosen as the model to study life expectancy in NTB; b) life expectancy in one region is directly impacted by life expectancy in adjacent regions; and c) a region's life expectancy is significantly impacted by its mean years of education and adjusted per capita expenditure, both of which can raise life expectancy in nearby regions. This link underscores the necessity of enacting policies that prioritize advancements in education and economic conditions in a particular location, while also taking into account the wider geographical context, to promote general well-being and life expectancy in adjacent regions.